Attitudes toward mental illness, mentally ill persons, and help-seeking among the Saudi public and sociodemographic correlates - Abolfotouh MA; Almutairi AF; Almutairi Z; Salam M; Alhashem A; Adlan AA; Modayfer O (Psychology Research and Behavior Management, 2019)
Mostafa A Abolfotouh,1 Adel F Almutairi,2 Zainab Almutairi,3 Mahmoud Salam,2 Anwar Alhashem,1 Abdallah A Adlan,4 Omar Modayfer5 1Research Training and Development Section, King Abdullah International Medical Research Center/ King Saud bin-Abdulaziz University for Health Sciences, Riyadh, Saudi Arabia; 2Science and Technology Unit, King Abdullah International Medical Research Center/ King Saud bin-Abdulaziz University for Health Sciences, Riyadh, Saudi Arabia; 3Stem Cells Donor Registry, King Abdullah International Medical Research Center/ King Saud bin-Abdulaziz University for Health Sciences, Riyadh, Saudi Arabia; 4Bioethics Section, King Abdullah International Medical Research Center/ King Saud bin-Abdulaziz University for Health Sciences, Riyadh, Saudi Arabia; 5Division of Mental Health, King Abdulaziz Medical City, Ministry of National Guard-Health Affairs, Riyadh, Saudi Arabia Background: It has been reported that the majority of individuals with mental illnesses (MIs) do not seek help. Few studies have focused on correlates of a positive attitude toward professional help-seeking for MI. This study aimed to determine levels of knowledge, perception, and attitudes toward MI, determine attitudes toward mental health help-seeking, and identify sociodemographic predictors of correct knowledge and favorable attitudes among the Saudi public. Methods: A cross-sectional survey was conducted on 650 Saudi adults aged >18 years who attended the Saudi Jenadriyah annual cultural and heritage festival during February 2016. The previously validated Attitudes to Mental Illness Questionnaire was used. Attitude to professional help-seeking was also assessed, using a tool retrieved from the World Mental Health Composite International Diagnostic Interview part II. Multiple regression analyses were applied, and statistical significance considered at P<0.05. Results: The majority of the Saudi public reported lack of knowledge about the nature of MI (87.5%, percentage mean score [PMS] 45.02±19.98), negative perception (59%, PMS 59.76±9.16), negative attitudes to MI (66.5%, PMS 65.86±7.77), and negative attitudes to professional help-seeking (54.5%, PMS 62.45±8.54). Marital status was a predictor of knowledge (t=–3.12, P=0.002), attitudes to MI (t=2.93, P=0.003), and attitudes to help-seeking (t=2.20, P=0.03). Attitudes to help-seeking were also predicted by sex (t=–2.72, P=0.007), employment (t=3.05, P=0.002), and monthly income (t=2.79, P=0.005). Perceptions toward the mentally ill were not predicted by these socioeconomic characteristics (P>0.05). Conclusion: The Saudi public reported lack of knowledge of MI and stigmatizing attitudes toward people with MI in relation to treatment, work, marriage, and recovery and toward professional help-seeking. Sociodemographic characteristics predicted correct knowledge and favorable attitudes, while Saudi culture was the likely factor behind negative judgments about mentally ill persons. Efforts to challenge this negative publicity and stigma through antistigma campaigns and public education through schools and media are recommended. Keywords: psychiatric illness, discrimination, people with mental illness, PWMI, stigma, antistigma, negative publicity, judgment of mental issues, professional help-seeking, social distance